Backbone conformation affects duplex initiation and duplex propagation in hybridisation of synthetic H-bonding oligomers. Issue 22 (23rd May 2018) - Iadevaia, Giulia; Núñez-Villanueva, Diego; Stross, Alexander E.; Hunter, Christopher A.
Abstract : Forming the first intramolecular H-bond is straightforward, but forming subsequent intramolecular interactions is difficult, because the backbone imposes more severe constraints. Abstract : Synthetic oligomers equipped with complementary H-bond donor and acceptor side chains form multiply H-bonded duplexes in organic solvents. Comparison of the duplex forming properties of four families of oligomers with different backbones shows that formation of an extended duplex with three or four inter-strand H-bonds is more challenging than formation of complexes that make only two H-bonds. The stabilities of 1 : 1 complexes formed between length complementary homo-oligomers equipped with either phosphine oxide or phenol recognition modules were measured in toluene. When the backbone is very flexible (pentane-1, 5-diyl thioether), the stability increases uniformly by an order of magnitude for each additional base-pair added to the duplex: the effective molarities for formation of the first intramolecular H-bond (duplex initiation) and subsequent intramolecular H-bonds (duplex propagation) are similar. This flexible system is compared with three more rigid backbones that are isomeric combinations of an aromatic ring and methylene groups. One of the rigid systems behaves in exactly the same way as the flexible backbone, but the other two do not. For these systems, the effective molarity for formation of the first intramolecular H-bond is the same as that found for the other two backbones, but additional H-bonds are not formed between the longer oligomers. The effective molarities are too low for duplex propagation in these systems, because the oligomer backbones cannot adopt conformations compatible with formation of an extended duplex.